2014
DOI: 10.1111/1754-9485.12211
|View full text |Cite
|
Sign up to set email alerts
|

Pathological manifestation of difference in washout pattern of adrenal hyperplasia on dynamic CT

Abstract: The key factors of washout pattern of AH on dynamic CT were CCR and TApre. The difference in constituent cell was associated with variability in APW of AH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous reports have shown that lipid-rich AAs do not demonstrate washout patterns different from those of lipid-poor AAs (4,8,10). On the other hand, although adrenal hyperplasia closely resembles AA in histology and is composed of both clear cells and compact cells, the variability in washout rates has been reported to be associated with differences in constituent cells of adrenal hyperplasia (11). That is, the washout rate of adrenal hyperplasia increases as the clear cell ratio (CCR) decreases or as tumor attenuation value of the pre-contrastenhanced CT image (TApre) increases.…”
mentioning
confidence: 92%
“…Previous reports have shown that lipid-rich AAs do not demonstrate washout patterns different from those of lipid-poor AAs (4,8,10). On the other hand, although adrenal hyperplasia closely resembles AA in histology and is composed of both clear cells and compact cells, the variability in washout rates has been reported to be associated with differences in constituent cells of adrenal hyperplasia (11). That is, the washout rate of adrenal hyperplasia increases as the clear cell ratio (CCR) decreases or as tumor attenuation value of the pre-contrastenhanced CT image (TApre) increases.…”
mentioning
confidence: 92%